The Impact of Voltage on Coils with 500 and 1000 Windings on the Performance of a Transformer in the Integrated Physics Laboratory at Campus B of Raden Fatah State Islamic University in Palembang: An Experiment of Physics Education - Juniarti, Rindi; Amelia, Vina; Jhoni, M (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2024)
The premise of this study is the lack of understanding regarding the distinction between utilizing 500 and 100 coils for transformers. This study investigates the influence of altering the number of windings on transformer coils on the generated voltage. The employed research methodology is experimental. The data analysis results indicate that a step-up transformer exhibits a primary voltage that is lower than its secondary voltage. By contrast, a step-down transformer exhibits a primary voltage that is greater than its secondary voltage. This is a result of the disparity in the number of windings between the secondary and primary coils. A step-up transformer is designed with a greater number of windings on the secondary coil, which leads to an increased secondary voltage. In contrast, a step-down transformer is designed with a greater number of windings on the primary coil, resulting in a reduced secondary voltage. This investigation validates the existence of a correlation between the quantity of windings on transformer coils and the voltage generated. Hence, the voltage of a transformer might fluctuate based on alterations in the quantity of windings on the coils.